English Proper Chants : Melody Edition - Ainslie, John, 1942- (Book collections on Project MUSE., 2015)
"Among the prayers of the Mass that vary from day to day (the propers), the Roman Missal includes an Entrance Antiphon and Communion Antiphon. English Proper Chants is a collection of beautiful, simple chant settings for these antiphons, with English texts, for all of the Sundays and Solemnities of the liturgical year."--Publisher's description.